2019
DOI: 10.1177/1947603519833136
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes after Revision of Autologous Chondrocyte Implantation to Osteochondral Allograft Transplantation for Large Chondral Defects: A Comparative Matched-Group Analysis

Abstract: Objective Osteochondral allograft transplantation (OCA) is a well-established procedure for patients with symptomatic cartilage defects in the knee. Revision to OCA after prior failed cartilage repair has shown similar clinical outcomes as primary OCA; however, most of the failed procedures were arthroscopic procedures for smaller defects. There is no literature investigating the clinical outcomes after OCA for prior failed autologous chondrocyte implantation (ACI) for the treatment of large chondral defects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“… c References 3 , 30 , 36 , 40 , 44 , 48 , 49 , 55 , 57 , 65 , 70 , 71 . d References 2 , 17 , 26 , 32 , 34 , 39 , 46 , 56 , 66 , 76 , 86 . …”
Section: Resultsunclassified
See 1 more Smart Citation
“… c References 3 , 30 , 36 , 40 , 44 , 48 , 49 , 55 , 57 , 65 , 70 , 71 . d References 2 , 17 , 26 , 32 , 34 , 39 , 46 , 56 , 66 , 76 , 86 . …”
Section: Resultsunclassified
“…78 Additionally, a robust body of literature supported the statement that OCAs can be used to revise previously failed cartilage restoration procedures. 17,32,34,39,46,56,76,86 Of these studies, a comparison of outcomes after primary OCA versus revision OCA after a failed cartilage procedure showed no significant difference and similar survival rates between the 2 cohorts. 32,39,56 A recent systematic review investigating outcomes of revision cartilage restoration procedures demonstrated that revision OCA consistently had similar results to primary OCA transplantation, even if the subchondral bone was affected.…”
Section: Indications For Osteochondral Allograftingmentioning
confidence: 99%
“…Two studies delayed RTP from 6 months to 8 to 12 months when MAT, HTO, DFO, TTO, or ACLR was performed in addition to OCA. 21,53 Twelve publications The Orthopaedic Journal of Sports Medicine Return-to-Play Criteria After OCA 5 included time to return to jumping or plyometric activity, with a mode of 6 months and a range of 6 months to 1 year. The timeline to return to sport/return to activity without restriction was reported in 37 studies, with a mode of 6 months and a range of 4 months to 1 year (Table 4).…”
Section: Rtp Criteriamentioning
confidence: 99%
“…However, (M-)ACI has two main limitations: Due to the limited number of healthy and non-degenerated chondrocytes, cells have to be expanded in vitro to achieve sufficient number of cells needed for the implantation (ACI: 1 million cells per cm², M-ACI: 20 million cells per cm 3 ) [10][11][12]. Further, chondrocytebased cartilage treatments, as well as microfracture techniques, result in formation of fibrocartilage, characterized by its inferior mechanical properties and thus lacking functional restoration compared to healthy hyaline cartilage [4,[13][14][15][16][17]. One approach to overcome the limitation of cell number for (M-)ACI treatment are MSC-chondrocyte co-cultures, e.g., 80 % MSC and 20 % chondrocytes, that reduces autologous chondrocyte cell number at same total cell density.…”
Section: Introductionmentioning
confidence: 99%